Innovation and democracy: the twin paradoxes - Grillo, Francesco; Nanetti, Raffaella (Area development and policy, 2020)
The 'innovation paradox' refers to the coexistence in the West over the last five decades of a steady decrease in the growth of productivity with the increase in the quantity of available information. These trends, which started with the invention of the internet, call for revisiting mainstream endogenous growth theory in an age dominated by information and communication technology. The weakness of the arguments used to justify the paradox, the unorthodox comparison with China and the history of the industrial revolutions point to the technological obsolescence of liberal democracy as the real explanation for the paradox. A debate on how to adapt Western institutions to a radically new context is launched.